Appendiceal mucinous cystadenocarcinoma with mural nodules of anaplastic carcinoma and K-RAS mutation - Gözde Kır; Billur Coşan Sarbay; Burçin Girgin; Filiz Özen (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Kır G, Coşan Sarbay B, Girgin B, Özen F. Appendiceal mucinous cystadenocarcinoma with mural nodules of anaplastic carcinoma and K-RAS mutation. Turk J Gastroenterol 2018; 29: 708-10.